Wrongful conduct of minors - FORTOVA, Lyubov (Journal of Education, Technology and Computer Science, 2014)
This article discusses the mechanisms and genealogy illegal behavior inchildren and adolescents. The role of the family as an institution of educationjuvenile delinquency prevention. Explores the role of social maturity of the personin the mechanism of formation of lawful behavior.